Prevalence and clinical implications of atrial fibrillation in patients hospitalized due to COVID-19: Data from a registry in Poland - Terlecki, Michał; Wojciechowska, Wiktoria; Klocek, Marek; Drożdż, Tomasz; Kocowska-Trytko, Maryla; Lis, Paweł; Pavlinec, Christopher; Pęksa, Jan W.; Kania, Michał; Siudak, Zbigniew; Januszewicz, Andrzej; Kreutz, Reinhold; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation (AF) is a common arrhythmia with increasing prevalence with respect to age and comorbidities. AF may influence the prognosis in patients hospitalized with Coronavirus disease 2019 (COVID-19). We aimed to assess the prevalence of AF among patients hospitalized due to COVID-19 and the association of AF and in-hospital anticoagulation treatment with prognosis. Methods and Results: We assessed the prevalence of AF among patients hospitalized due to COVID-19 and the association of AF and in-hospital anticoagulation treatment with prognosis. Data of all COVID-19 patients hospitalized in the University Hospital in Krakow, Poland, between March 2020 and April 2021, were analyzed. The following outcomes: short-term (30-days since hospital admission) and long-term (180-days after hospital discharge) mortality, major cardiovascular events (MACEs), pulmonary embolism, and need for red blood cells (RBCs) transfusion, as a surrogate for major bleeding events during hospital stay were assessed. Out of 4,998 hospitalized patients, 609 had AF (535 pre-existing and 74 de novo). Compared to those without AF, patients with AF were older and had more cardiovascular disorders. In adjusted analysis, AF was independently associated with an increased risk of short-term (p=0.019, Hazard Ratio [(HR]) 1.236; 95%CI 1.035-1.476) and long-term mortality (Log-rank p<0.001) as compared to patients without AF. The use of novel oral anticoagulants (NOAC) in AF patients was associated with reduced short-term mortality (HR 0.14; 95%CI 0.06-0.33, p<0.001). Moreover, in AF patients, NOAC use was associated with a lower probability of MACEs (Odds Ratio 0.3; 95%CI 0.10-0.89, p=0.030) without increase of RBCs transfusion. Conclusions: AF increases short- and long-term risk of death in patients hospitalized due to COVID-19. However, the use of NOACs in this group may profoundly improve prognosis.